Spillovers from conditional cash transfer programs: Bolsa Família and crime in urban Brazil - Laura Chioda; Jo\~ao M. P. de Mello; Rodrigo R. Soares (Institute for the Study of Labor (IZA), 2012)
This paper investigates the impact of Conditional Cash Transfer (CCT) programs on crime. Making use of a unique dataset combining detailed school characteristics with time and geo-referenced crime information from the city of S\~ao Paulo, Brazil, we estimate the contemporaneous effect of the Bolsa Família program on crime. We address the endogeneity of CCT coverage by exploiting the 2008 expansion of the program to adolescents aged 16 and 17. We construct an instrument that combines the timing of expansion and the initial demographic composition of schools to identify plausibly exogenous variations in the number of children covered by Bolsa Família. We find a robust and significant negative impact of Bolsa Família coverage on crime. The evidence suggests that the main effect works through increased household income or changed peer group, rather than from incapacitation from time spent in school.
urn:nbn:de:101:1-201206146460
Keywords: I28; I38; K42; 330; conditional cash transfer; Bolsa Família; crime; education; schooling; Brazil; Sozialhilfe; Familienpolitik; Wirkungsanalyse; Kriminalität; Schätzung; Brasilien